Joint PAPR Reduction and Physical Layer Security Enhancement in OFDMA-PON - Zhang, Wei (2016)
For joint peak-to-average power ratio (PAPR) reduction and physical layer security enhancement, we propose a chaos IQ-encryption-based optimal frame transmission technique in an orthogonal frequency-division multiple access-based passive optical network (OFDMA-PON). The chaos IQ-encryption technique is utilized to enhance the physical layer security. In encrypting, the in-phase (I) and quadrature-phase (Q) parts of the quadrature amplitude modulation (QAM) symbols are coded with two phase sequences separately, which are generated using a 2-D logistic map. The encrypted OFDM symbols comprise an OFDM frame, and the frame with the minimum PAPR is transmitted to the optical network unit side. Thus, the transmitted OFDM signal is of a joint low PAPR and high physical layer security. In the demonstration, an 11.32-Gb/s encrypted 16 QAM OFDM signal has been experimentally transmitted over 25-km standard single mode fiber in an intensity-modulation/direct-detection OFDMA-PON.